Genetic dissection of quantitative trait loci for flag leaf size in bread wheat (Triticum aestivum L.) - Chen, Liangen; Xu, Zhibin; Fan, Xiaoli; Zhou, Qiang; Yu, Qin; Liu, Xiaofeng; Liao, Simin; Jiang, Cheng; Lin, Dian; Ma, Fang; Feng, Bo; Wang, Tao (Frontiers in Plant Science, 2022)
Flag leaf size is a crucial trait influencing plant architecture and yield potential in wheat. A recombinant inbred line (RIL) population derived from the cross of W7268 and Chuanyu 12 was employed to identify quantitative trait loci (QTL) controlling flag leaf length (FLL), flag leaf width (FLW), and flag leaf area (FLA) in six environments and the best linear unbiased estimator (BLUE) datasets. Using a 55 K SNP-based genetic map, six major and stable QTL were detected with 6.33–53.12% of explained phenotypic variation. Except for QFlw.cib-4B.3, the other five major QTL were co-located within two intervals on chromosomes 2B and 2D, namely QFll/Fla.cib-2B and QFll/Flw/Fla.cib-2D, respectively. Their interactions and effects on the corresponding traits and yield-related traits were also assessed based on flanking markers. QFll/Fla.cib-2B showed pleiotropic effects on spikelet number per spike (SNS). QFlw.cib-4B.3 and QFll/Flw/Fla.cib-2D had effects on grain number per spike (GNS) and thousand-grain weight (TGW). Comparison analysis suggested that QFll/Fla.cib-2B was likely a new locus. Two candidate genes, TraesCS2B03G0222800 and TraesCS2B03G0230000, associated with leaf development within the interval of QFll/Fla.cib-2B were identified based on expression-pattern analysis, gene annotation, ortholog analysis, and sequence variation. The major QTL and markers reported here provide valuable information for understanding the genetic mechanism underlying flag leaf size as well as breeding utilization in wheat.